Bibliometric and visual analysis of microglia-related neuropathic pain from 2000 to 2021 - Zhang, Shun-Bai; Zhao, Guang-Hai; Lv, Tian-Run; Gong, Chao-Yang; Shi, Yong-Qiang; Nan, Wei; Zhang, Hai-Hong (Frontiers in Molecular Neuroscience, 2023)
Background Microglia has gradually gained researchers’ attention in the past few decades and has shown its promising prospect in treating neuropathic pain. Our study was performed to comprehensively evaluate microglia-related neuropathic pain via a bibliometric approach. Methods We retrospectively reviewed publications focusing on microglia-related neuropathic pain from 2000 to 2021 in WoSCC. VOS viewer software and CiteSpace software were used for statistical analyses. Results A total of 2,609 articles were finally included. A steady increase in the number of relevant publications was observed in the past two decades. China is the most productive country, while the United States shares the most-cited and highest H-index country. The University of London, Kyushu University, and the University of California are the top 3 institutions with the highest number of publications. Molecular pain and Pain are the most productive and co-cited journals, respectively. Inoue K (Kyushu University) is the most-contributed researcher and Ji RR (Duke University) ranks 1st in both average citations per article and H-index. Keywords analyses revealed that pro-inflammatory cytokines shared the highest burst strength. Sex differences, neuroinflammation, and oxidative stress are the emerging keywords in recent years. Conclusion In the field of microglia-related neuropathic pain, China is the largest producer and the United States is the most influential country. The signaling communication between microglia and neurons has continued to be vital in this field. Sexual dimorphism, neuroinflammation, and stem-cell therapies might be emerging trends that should be closely monitored.